Could the endoscopic resection of a large rectal leiomyoma be an effective and safe technique? - Sinagra, Emanuele; Tomasello, Giovanni; Pompei, Giancarlo; Menozzi, Massimo; Mandalà, Stefano; Rossi, Francesca; Martorana, Guido; Messina, Marco; Rizzo, Aroldo Gabriele; Calvaruso, Marco; Morreale, Gaetano Cristian; Amvrosiadis, Georgios; et al. (European Journal of Oncology and Environmental Health, 2017)
Rectal leiomyomas are a rare conditions, with low reported incidence in literature and constitute about 0.1% of rectal tumours; in fact rectal leiomyomas occur in approximately 1 out of 2000-3000 rectal tumors. We report on a patient with a 3 cm semi-pedunculated colonic leiomyoma, which was successfully removed by endoscopic polypectomy after normal saline-epinephrine submucosal injection. When we encounter a tumor during a colonoscopic examination, we usually evaluate the tumor carefully and perform an endoscopic resection when we judge it is appropriate. When a symptomatic smooth muscle tumors smaller than 2 cm are incidentally found on colonoscopy, surgical resection is unnecessary. Furthermore, if a tumor can be lifted with a snare and it is either pedunculated or semi-pedunculated, endoscopic resection might be a safe option. For those tumors with wide-based or exoluminal growth, endoscopic removal should be avoided due to the higher risks of bleeding and perforation.The histological findings of the resected tumor are important. If there is any malignant element that can not be completely eradicated, we would suggest surgical treatment. We believe our process allows to avoid unnecessary surgery and reduces medical costs.